"[My counselor] knows stuff about me, but [my natural mentor] actually knows me": Distinguishing characteristics of youth's natural mentoring relationships. (April 2020) - Deutsch, Nancy L.; Mauer, Victoria A.; Johnson, Haley E.; Grabowska, Anita A.; Arbeit, Miriam R.
Highlights: Having time and space for a relationship to develop is key. Adults intentionally using time and space to develop relationships is critical. A feeling of the adult existing across contexts can foster relational development. A psychological sense of shared time & space may be important across transitions. Trust, particularly bidirectional trust was important for many youth. Cultivating safe & authentic relationships for youth to express themselves was key. Specific adult practices fostered safe and authentic relationships. These include: peer-like nature, listening, lack of judgment, validation of self. Abstract: Adults play important roles in the lives of adolescents, serving as role models, sources of social support, and providers of social capital. Natural mentoring relationships (NMRs), relationships between adults and youth that rise to a level of significance for the youth, have a positive impact on youth outcomes in a number of academic, socioemotional, and health related areas. Yet despite the importance of NMRs to youth development, there is little research on how NMRs develop or what factors are associated with a relationship becoming an NMR. This study uses in-depth qualitative interviews with adolescents across five time points to explore the characteristics of youth-adult relationships that develop into NMRs, and the psychosocial processes and actions which transform a naturally occurring relationship into an NMR. Findings from our study suggest that by intentionally using time and space with youth as an opportunity to cultivate safe and authentic spaces and build trust, adults can encourage the development of NMRs with adolescents.